The science of monetary policy: An imperfect knowledge perspective - Stefano Eusepi; Bruce Preston (Federal Reserve Bank of New York, 2016)
New Keynesian theory identifies a set of principles central to the design and implementation of monetary policy. These principles rely on the ability of a central bank to manage expectations precisely, with policy prescriptions typically derived under the assumption of perfect information and full rationality. However, the challenging macroeconomic environment bequeathed by the financial crisis has led many to question the efficacy of monetary policy, and, particularly, to question whether central banks can influence expectations with as much control as previously thought. In this paper, we survey the literature on monetary policy design under imperfect knowledge and asses to what degree its policy prescriptions deviate from the rational expectations benchmark.
Keywords: E31; E32; E52; 330; monetary policy; expectations formation; learning